Biological Trend in Contemporary Criminology (Archives of Criminology, 1984)
Discussions of the relationship between biological factors and criminality have a long tradition in criminology. During the first stage of development of positivistic criminology, they constituted a predominant trend in the study of etiology of crime and delinquency. Then, with the future development of this school, they became one of its major lines, together with the study of cultural variables. The controversions between adherents of these two trends of the positivistic school resolve themselves into the essential question nature or nature. In other  words, is a given human behaviour (e.g., criminal) a result of the man’s biological equipment, or was it influenced by the course of the process of upbringing in the broad sense. In different periods one or the other of these approaches predominated. Now it is generally considered that both nature and nurture regulate human behaviour in the process of constant interaction.       Contemporary students of the role of biological factors in the etiology of crime abstain in general from attributing to these factors the conclusive role in  the formation of criminal behaviour. Instead, they maintain that in certain circumstances a given biological factor may contribute to the appearance of behaviour which  departs from the norm. In principle, biological factors may be divided into those which contribute more directly to the appearance of criminal behaviour, and those which exercise only an indirect influence - in interaction with environmental variables. The first group consists of such variables as tumours and other pathological injuries of the central nervous system, some forms of epilepsy and certain types of hormonal disorders. In a sense, all the above variables are directly connected with behaviour disorders which, in certain situations, may lead to the appearance of criminal behaviour. These regularities concern a small percent of offenders only, so general conclusions can not be drawn on this ground as regards biological conditions of delinquency.     Among biological variables which influence behaviour problems (including criminal behaviour) indirectly, in interaction with environmental  variables, the following are  included in general: effect of prenatal and birth complications on the development of the child's central nervous system, minimal brain dysfunction and  their correlates factors connected with heredity, chromosomal abnormalities (particularly XYY syndrome), and various psychophysiological variables related to the conditioning of behaviour. These variables can not be  said to cause in themselves behaviour disorders favourable to crime and delinquency; it is imperative that particular environmental conditions arise for these disorders to appear. Thus in this case we deal with the effecti of different variables conditioned by class or environment, on the individual's biological formation and the role of the relationship between biological and environmental variables in shaping of man's adaptivity, including his ability to behave according to the norm.      In the present article, a review of the contemporary studies of the above problem has been made.      It has repeatedly been discovered that, in environment which is economically and socially unpriviledged, there are decidedly more prenatal  and brith complications which are favourable to injuries of the child's central nervous system. Such injuries positively hinder social adaptation,  particularly if the influence of environment in which the child is brought up is negative. The same may be said about the role of minimal brain dysfunction in the  formation of the child's social attitudes. Here also, the influence of the environment may intensify the effect of the biological factor. In the studies of genetic determination of abnormal behaviour, results were obtained which indicate that in the etiology of such behaviour, hereditary factors are of some importance, while environment often  „intensifies” the effect of genetic  factors.      The approach which is characterized by the search for the connection of both biological and environment variables with behaviour disorders (including criminal behaviour) has a strong position in Polish criminology thanks to the works of Professor Batawia and his associates.     In the final of the article, the importance of disclosures as regards the role of biological factors in the etiology of delinquent behaviour in the field of crime prevention has been discussed.